Development of European standards for evaluative reporting in forensic science: The gap between intentions and perceptions. (January 2017) - Biedermann, Alex; Champod, Christophe; Willis, Sheila
Criminal justice authorities of EU countries currently engage in dialogue and action to build a common area of justice and to help increase the mutual trust in judicial systems across Europe. This includes, for example, the strengthening of procedural safeguards for citizens in criminal proceedings by promoting principles such as equality of arms. Improving the smooth functioning of judicial processes is also pursued by works of expert working groups in the field of forensic science, such as the working parties under the auspices of the European Network of Forensic Science Institutes (ENFSI). This network aims to share knowledge, exchange experiences and come to mutual agreements in matters concerning forensic science practice, among them the interpretation of results of forensic examinations. For example, through its Monopoly Programmes (financially supported by the European Commission), ENFSI has funded a series of projects that come under the general theme 'Strengthening the Evaluation of Forensic Results across Europe'. Although these initiatives reflect a strong commitment to mutual understanding on general principles of forensic interpretation, the development of standards for evaluation and reporting, including roadmaps for implementation within the ENFSI community, are fraught with conceptual and practical hurdles. In particular, experience through consultations with forensic science practitioners shows that there is a considerable gap between the intentions of a harmonised view on principles of forensic interpretation and the way in which works towards such common understanding are perceived in the community. In this paper, we will review and discuss several recurrently raised concerns. We acknowledge practical constraints such as limited resources for training and education, but we shall also argue that addressing topics in forensic interpretation now is of vital importance because forensic science continues to be challenged by proactive participants in the legal process that tend to become more demanding and less forgiving.